Method of extrapolation the probability characteristics of the traffic noise backgroundin local computer networks - Андреєв, О. В. (Problems of Informatization and Control, 2013)
A new method for extrapolation the probability characteristics of the traffic noise background in localcomputer networks, which allows for the prior probability values of the observed characteristics of thetwo points to forecast the probability characteristics for the third point, the value of which would bepredicted. Preliminary values of the probability of the observed characteristics of the two points aredetermined by the training set of traffic of small size, which is taken at the initial site traffic monitoring.Comparative analysis of the relative errors of the characteristics of the observed traffic and extrapolatedusing the proposed method shows acceptable practice for the relative errors.